Comparative Analysis of Durability and Failure Rates in Feldspathic, Lithium Disilicate, and Alumina Veneers - Long-term Results - Armendáriz Tobar, Verónica Daniela (Archive of Orofacial Data Science, 2025)
AIM: The objective of this study is to compare the durability and failure rates of feldspathic, lithium disilicate, and alumina veneers following treatment. METHODS: A comprehensive search of the dental literature was conducted via the Pubmed database. From the selected studies, survival rates of feldspathic, lithium disilicate, and alumina veneers were extracted, along with failure rates of fracture, chipping, debonding, marginal adaptation, discoloration, staining, and secondary caries. RESULTS: The average observation period was 10 years. The estimated survival rates were 95.3% for feldspathic, 95% for lithium disilicate, and 93% for alumina. The analysis of failure rates revealed the following: fractures occurred at rates ranging from 0.9% over 3.4 years to 5% after 11 years for feldspathic veneers. Lithium disilicate showed an average fracture rate of 3.6% over 9.8 years, whereas alumina had a 6.6% fracture rate over the same period. Chipping was higher for alumina veneers (16.5%) compared to feldspathic (4%) and lithium disilicate (3.6%). All three types of veneers experienced low debonding rates (1-2%). Marginal adaptation issues were more prevalent in alumina and feldspathic veneers than in lithium disilicate. Marginal discoloration was higher in alumina veneers compared to other types. Staining and secondary caries were observed at low average percentages across all veneer types. CONCLUSION: Feldspathic, lithium disilicate, and alumina veneers exhibit high survival rates and durability. The most frequent failures are fractures, chipping, and marginal discoloration, while debonding, staining, and secondary caries are rare complications.